Changes in the transcriptional activity of the entero-insular axis genes in streptozotocin-induced diabetes and after the administration of TNF-α non-selective blockers - Degen, A. S.; Krynytska, I. Y.; Kamyshnyi, A. M.; Деген, Анна Сергіївна; Камишний, Олександр Михайлович (My University, 2020)
The aim of the present study was to investigate the transcriptional activity of the GLP1R, DPP-4, SGLT-1, INSR, and IGF-1R genes in GALT cells of rats with streptozotocin-induced diabetes in both untreated and treated with pentoxifylline, as a non-specific blocker of TNF-α. Methods. The expression of GLP-1R, DPP-4, SGLT-1, INSR, and IGF-1R genes in GALT cells of rats was studied by real time quantitative polymerase chain reaction. Results. It was shown that the development of diabetes was accompanied by the decrease of GLP-1R and an increase of DPP-4 genes expression in rat ileum. The administration of pentoxifylline to diabetic animals led to an increase in the transcriptional activity of GLP-1R on the 4th week and decrease in transcriptional activity of DPP-4 on the 2nd and 4th weeks of the experiment. An increase in the normalized expression of SGLT-1 on the 4th week of the experimental diabetes was also noted, while the administration of pentoxifylline to diabetic animals did not lead to significant changes in this index. The transcriptional activity of the INSR and IGF-1R genes was reduced in diabetic rats and the administration of the non-specific TNF-α blocker – pentoxifylline led to a significant increase only for INSR gene in animals on the 4th week of the experimental diabetes. Conclusions. The expression of incretins, glucose transporters, and pro-inflammatory cytokines (e.g. TNF-α) in immune cells may be used as markers of several autoimmune pathologies progression such as type 1 diabetes due to their effect on the balance of pro- and anti-inflammatory factors.
Keywords: entero-insular axis; mRNA; diabetes mellitus; pentoxifylline